Implementation of Integrated Health Posts and Maternal and Child Health Counseling in Sukajati Village, Haurgeulis District, Indramayu Regency - Galih Eka Rajasa; Tobiin (Al-Hukumah: Jurnal Ilmu Pemerintahan dan Studi Islam, 2025)
Posyandu is a form of community-based health efforts that are managed and organized from, by, for and with the community in organizing health development, in order to empower the community and provide convenience to the community in obtaining basic health services. The purpose of writing this article is to find out the Implementation of Posyandu and Maternal and Child Health Counseling in Sukajati Village, Haurgeulis District, Indramayu Regency. The methods used include, namely The methods used in the work program of posyandu activities and counseling are socialization and interactive. Socialization is used when presenting the material on the importance of providing an understanding of Maternal and Child Health to the Sukajati Village Community. The results of this activity are that the Posyandu program and maternal and child health counseling in Sukajati Village have succeeded in increasing public awareness of health and nutrition, as well as reducing the problem of malnutrition. This program helps create a healthier and more educated community. It is recommended that the community continue sustainable programs for the welfare of maternal and child health in the long term.